STUDI PENCAPAIAN TUGAS PERKEMBANGAN REMAJA PADA SISWA-SISWI SMAN 1 PORONG - Widy Setyowati (LPPM Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2019)
Developmental tasks is the tasks that come from the expectations of society must be full filled by individual at every stage of development, the developmental task of adolescent does not simple and must be achieved in ashort periode, if the fails will make unhappiness experience in adulthood. This study was conducted to determine the achievement of developmental tasks achieve a more mature relationship with peers and receive physical circumstances and effectively utilize the body at the age of 15-18 years old. The research design is descriptive, 120 sample is adolescents aged 15-18 years in SMAN 1 Porong with random sampling technique samples. The study was conducted from Jue 20-25, 2016. Data were collected using questionnaire. The result showed that most of the adolescents (62.5%) achieved the moderate indicator for developmental tasks to achieve more mature relationship with peers and to self received and effectively utilize the body. Most (55%) teenagers achieved only moderate indicator. The conclution is that teenagers have not been maximized in achieving the two developmental tasks that should have been achieved in their teens. Nurses are expected to be oriented towards healthy clients with high-risk vulnerable conflicts in providing community nursing care at the school level. Schools can help adolescents to recognize and carry out developmental tasts.